Vertically Stacked Full Color Quantum Dots Phototransistor Arrays for High‐Resolution and Enhanced Color‐Selective Imaging. Issue 2 (23rd October 2021) - Kim, Jaehyun; Jo, Chanho; Kim, Myung‐Gil; Park, Gyeong‐Su; Marks, Tobin J.; Facchetti, Antonio; Park, Sung Kyu
Abstract: Color‐selective multifunctional and multiplexed photodetectors have attracted considerable interest with the increasing demand for color filter‐free optoelectronics which can simultaneously process multispectral signal via minimized system complexity. The low efficiency of color‐filter technology and conventional laterally pixelated photodetector array structures often limit opportunities for widespread realization of high‐density photodetectors. Here, low‐temperature solution‐processed vertically stacked full color quantum dot (QD) phototransistor arrays are developed on plastic substrates for high‐resolution color‐selective photosensor applications. Particularly, the three different‐sized/color (RGB) QDs are vertically stacked and pixelated via direct photopatterning using a unique chelating chalcometallate ligand functioning both as solubilizing component and, after photoexposure, a semiconducting cement creating robust, insoluble, and charge‐efficient QD layers localized in the a‐IGZO transistor region, resulting in efficient wavelength‐dependent photo‐induced charge transfer. Thus, high‐resolution vertically stacked full color QD photodetector arrays are successfully implemented with the density of 5500 devices cm –2 on ultrathin flexible polymeric substrates with highly photosensitive characteristics such as photoresponsivity (1.1 × 10 4 AW –1 ) and photodetectivity (1.1 × 10 18 Jones) as well as wide dynamic ranges (>150 dB). Abstract : Monolithic integration of vertically stacked red (R), green (G), and blue (B) quantum dots (QDs), from chalcometallate RGB QD precursor films, with amorphous oxide semiconductor indium‐gallium‐zinc‐oxide phototransistor arrays for high‐resolution active‐matrix driving of color‐selective multispectral photodetection is demonstrated. Efficient QD connectivity for reduced trap density and photopatternability essential for pixelation are achieved, which result in ultrahigh photosensitive optoelectronic properties.